POLITIK HUKUM PERBANKAN dI INdONESIA PAdA ERA GLOBAL - Dewi Nurul Musjtari (Yustisia, 2014)
The purpose of writing this article is to know the politics of banking law in Indonesia after the entry intoforce of Islamic Banking Act and determine the political direction of the law to resolve problems thatarise in the practice of banking in Indonesia in the global era. This article uses literature study on legalproducts namely Regulatory associated with banking and Islamic banking. This article is based on apolitical perspective. Formulation is based on written materials such as Banking Law and Islamic banking,the Constitutional Court’s decision, scientific papers relevant to the issues and the results of interviews.To obtain the data carried on the product literature study of legislation, decrees and interview. Existinglegal materials, then analyzed in legal political perspective with qualitative descriptive method. The resultis political banking law in Indonesia after the enactment of Law No. 21 Th. 2008 and the ConstitutionalCourt Decision No.93/PUU-X/2012, the absolute competence dispute resolution Islamic banking in thereligious court. Legal politics can solve problems that arise in the practice of banking in Indonesia, withthe availability of judicial review mechanisms and constitutional review. Judicial institutions in question,namely the establishment of the Constitutional Court as the guardian of the constitution and respondto community development will be a fair legal certainty is still relevant to be protected. The existence ofIslamic banking as part of the national banking system is one of the financial institutions that can supportIndonesia in the face of global challenges and can be used to enhance the economic competitivenessand Indonesia’s rating in the arena of economic competition in the global era.